Desarrollo folicular en ovejas durante el ciclo estral natural e inducido con prostaglandinas - Uribe-Velásquez, Luis Fernando; Oba, Eunice [UNESP]; Souza, Maria Inês Lenz; Vélez-Marín, Miryam; Correa-Orozco, Adriana (My University, 2010)
The follicular development was evaluated in ovine females during natural and prostaglandin-F2α (PG) induced estrous cycle. Ewes were randomly divided in two treatments (n=7/treatment): T1 with natural cycle and T2 synchronized with two injections of PG. From one day before PG injection until next ovulation, daily transrectal ultrasonography was done. All follicles >2 mm were assessed. During the interovulatory intervals, follicular growth and regression occurred in a wave like pattern (2-3 waves). The maximum diameter of the largest follicle of the first wave was greater in T1 (5.83 ± 0.31 mm) compared with T2 (5.0 ±0.1 mm; P<0.01), but there was no significant difference among the emergency day of largest follicle, during the growth phase of the follicular waves. The duration of the plateau phase in wave 2 differed between the two treatments (P<0.05) showing 0.83 ± 0.31 and 1.83 ± 0.17 d, for natural and synchronized treatment, respectively. Growth rate did not differ between treatments. Presence of new luteal tissue was detected on day 3 after ovulation. In conclusion, the follicular development was similar in female ovine during natural and PG induced estrous cycle.
Follicular development in ewes during natural and prostaglandins induced estrous cycle
Keywords: Estrous; Follicles; Prostaglandins; Synchronization